2021
DOI: 10.1111/ped.14608
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen elevates unbound bilirubin levels by the glucose oxidase‐peroxidase method

Abstract: Background Acetaminophen is widely administered to neonates but its effect on unbound bilirubin (UB) levels remains unclear. The aim of this study was to clarify whether administration of acetaminophen is related to an elevation of UB levels. Method Infants with a birthweight of ˂1,500 g admitted to our neonatal intensive care unit between January 2017 and April 2020 were retrospectively reviewed. Seventy‐one infants were enrolled, five of whom had received acetaminophen. Clinical data were analyzed when the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…We read with great interest the recent article by Ichimura et al, who reported that high unbound bilirubin (UB) levels observed in infants who were administered acetaminophen (ACP) as measured by the glucose oxidase-peroxidase (GOD-POD) method. 1 The authors concluded that these elevated UB levels were due to an effect of ACP on the GOD-POD method. 2 However, serum ACP concentrations were not measured in their study infants.…”
mentioning
confidence: 99%
“…We read with great interest the recent article by Ichimura et al, who reported that high unbound bilirubin (UB) levels observed in infants who were administered acetaminophen (ACP) as measured by the glucose oxidase-peroxidase (GOD-POD) method. 1 The authors concluded that these elevated UB levels were due to an effect of ACP on the GOD-POD method. 2 However, serum ACP concentrations were not measured in their study infants.…”
mentioning
confidence: 99%